Analysis based on questionnaire on the situation of fruit producers in the South and South-East area of the country - Rodica Chetroiu; Lidia Iurchevici (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 8th Edition of the International Symposium, November 2017, Bucharest, 2017)
The paper is part of the research undertaken under ADER Project 16.1.2 - Models of development of short chains of valorisation on the pathway primary production-services-warehousing-processing-marketing, Stage 3. To diagnose the situation of fruit producers, a number of 153 questionnaires were applied in 5 counties from representative areas for fruit production, namely Dâmboviðta, Argeðs, Prahova, Vâlcea, Constanðta. After centralizing the results, it emerged that 79.1% of the fruit growers surveyed started their activity after 1990, and 55% of them are not registered in any legal form. Regarding the size of holdings owned, three-quarters of farmers hold between 1-5 ha. As a structure, the apple orchards rank first (29%), followed by plums (26%), the rest are pear, peaches, nuts and others. 65% of the orchards are cultivated exclusively with native varieties, the planting material being mostly self-produced and only 1% have exclusively imported varieties. Mechanized agricultural works are carried out in a proportion of 76% by own means, and in terms of land fertilization, 63% of respondents apply both chemical and organic fertilizers and only 26% apply only natural fertilizers. Organic phytosanitary treatments are only applied by 12% of producers and 80% do not irrigate orchards.
Keywords: D13; D23; L11; 330; fruits; questionnaire; apple; orchards